Wage Subsidies in a Program for Economic Inclusion and Growth - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2011)
This paper is in three parts. The first part discusses the workings of a wage subsidy scheme in boosting employment and earnings of workers. The second part reviews the empirical evidence on the effectiveness of wage subsidy schemes in countries that have implemented them both as countercyclical policies as well as structural programs to boost long-term earnings and employment of low wage workers. The third part looks at Singapore as a case study of how wage subsidies have been used in a program for generating economic inclusion both in the context of growth as well as in the context of business fluctuations.